Correlation between Metabolite of Prostaglandin E2 and the incidence of colorectal adenomas - Jiang, Jia; Li, Anjie; Lai, Xiaolian; Zhang, Hanqun; Wang, Chonghong; Wang, Huimin; Li, Libo; Liu, Yuncong; Xie, Lu; Yang, Can; Zhang, Cui; Lu, Shuoyan; et al. (Frontiers in Oncology, 2023)
Colorectal cancer is a common malignancy, and the incidence and mortality rates continue to rise. An important factor in the emergence of inflammation-induced colorectal carcinogenesis is elevated cyclooxygenase-2. Prostaglandin E2 (PGE2) over-production is frequently equated with cyclooxygenase-2 gene over-expression. PGE2 can be assessed by measuring the level of prostaglandin’s main metabolite, PGE-M, in urine. Colorectal adenoma is a precancerous lesion that can lead to colorectal cancer. We conducted research to evaluate the association between urinary levels of the PGE-M and the risk of colorectal adenomas. In a western Chinese population, we identified 152 cases of adenoma and 152 controls patients without polyps. Adenoma cases were categorized into control, low-risk and high-risk groups. There was no significant change in PGE-M levels, between the control group and the low-risk adenoma group. In the high-risk group, the PGE-M levels were 23% higher than the control group. When compared to people with the lowest urine PGE-M levels (first quartile), people with greater urinary PGE-M levels had a higher chance of developing high-risk colorectal adenomas, with an adjusted odds ratio (95% CI) of 1.65 (0.76-3.57) in the fourth quartile group, (p= 0.013). We conclude urinary PGE-M is associated with the risk of developing high-risk adenomas. Urinary PGE-M level may be used as a non-invasive indicator for estimating cancer risk.